Myricetin attenuates lipopolysaccharide‐stimulated activation of mouse bone marrow‐derived dendritic cells through suppression of IKK/NF‐κB and MAPK signalling pathways. (12th June 2012) - Fu, Ru‐Huei; Liu, Shih‐Ping; Chu, Ching‐Liang; Lin, Ya‐Hsien; Ho, Yu‐Chen; Chiu, Shao‐Chih; Lin, Wei‐Yong; Shyu, Woei‐Cherng; Lin, Shinn‐Zong
Abstract: BACKGROUND: Myricetin is a naturally occurring flavonoid that is found in many fruits, vegetables, teas and medicinal herbs. It has been demonstrated to have anti‐inflammatory properties, but, to date, no studies have described the immunomodulatory effects of myricetin on the functions of dendritic cells (DCs). The aim of this study was to evaluate the potential for myricetin to modulate lipopolysaccharide (LPS)‐stimulated activation of mouse bone marrow‐derived DCs. RESULTS: Our experimental data showed that treatment with myricetin up to 10 µg mL −1 does not cause cytotoxicity in cells. Myricetin significantly decreased the secretion of tumour necrosis factor‐α, interleukin‐6 and interleukin‐12p70 by LPS‐stimulated DCs. The expression of LPS‐induced major histocompatibility class II, CD40 and CD86 on DCs was also inhibited by myricetin, and the endocytic and migratory capacity of LPS‐stimulated DCs was blocked by myricentin. In addition, LPS‐stimulated DC‐elicited allogeneic T‐cell proliferation was reduced by myricetin. Moreover, our results confirmed that myricetin attenuates the responses of LPS‐stimulated activation of DCs via suppression of IκB kinase/nuclear factor‐κB and mitogen‐activated protein kinase‐dependent pathways. CONCLUSION: Myricetin has novel immunopharmacological activity, and modulation of DCs by myricetin may be an attractive strategy for the treatment of inflammatory and autoimmune disorders, and for transplantation. Copyright © 2012 Society of Chemical Industry